Innovation management practices: cross‐sectorial adoption, variation, and effectiveness. (25th January 2016) - Tidd, Joe; Thuriaux‐Alemán, Ben
Abstract : Innovation management practices (IMPs) represent the codification of innovation research and management experience, and offer the potential to improve innovation performance. Studies suggest limited awareness of IMPs amongst practitioners, and even lower rates of application, and we know little of their perceived importance or effectiveness in different industries. Our paper assesses the use of eight functional groups of IMPs within and across sectors, drawing on a sample of 292 valid responses, based on survey data and associated and validated case studies. Overall, we find significant variation in usage patterns across sectors and a positive relationship between the use of IMPs and innovation outcomes. However, only a very small number of innovation management practices can be considered to be universally positive, including external technology intelligence gathering, and technology and product portfolio management. We find that the use and effectiveness of most IMPs varies by industry. This suggests there is significant potential for the more widespread application of some IMPs, but that managers must be highly selective.